Adipose Mesenchymal Stromal Cell-Derived Exosomes Prevent Testicular Torsion Injury via Activating PI3K/AKT and MAPK/ERK1/2 Pathways. (16th June 2022) - Liu, Hengchen; Shi, Manyu; Li, Xiangqi; Lu, Wenjun; Zhang, Mingzhao; Zhang, Tingting; Wu, Yang; Zhang, Zenan; Cui, Qingbo; Yang, Shulong; Li, Zhaozhu
Abstract : Adipose mesenchymal stromal cell-derived exosomes (ADSC-Exos) have shown great potential in the treatment of oxidative stress induced by ischemia-reperfusion injury. However, alleviation of testicular torsion injury by ADSC-Exos has not been reported. Therefore, we investigated the protective effect of ADSC-Exos against testicular torsion-detorsion injury. ADSC-Exos were isolated by ultracentrifugation and injected into torsion-detorsion-affected testes of rats. H&E staining and sperm quality were used to evaluate the therapeutic effects of ADSC-Exos, and tissue oxidative stress was measured by determining MDA and SOD levels. In addition, TUNEL staining and immunohistological analysis (Ki67, Cleaved Caspase-3, IL-6, IL-10, CCR7, and CD163) were used to clarify the effects of ADSC-Exos on spermatogenic cell proliferation, apoptosis, and the inflammatory microenvironment in vivo . Possible signaling pathways were predicted using sequencing technology and bioinformatics analysis. The predicted signaling pathways were validated in vitro by assessing the proliferation (EdU assay), migration (transwell assay and scratch test), and apoptosis (flow cytometry, TUNEL staining, and western blotting) of spermatogenic cells. The results showed that ADSC-Exos alleviated testicular torsion-detorsion injury by attenuating oxidative stress and the inflammatory response. In addition, ADSC-Exos promoted the proliferation and migration of spermatogenic cells and inhibited their apoptosis by activating the PI3K/AKT and MAPK/ERK1/2 signaling pathways.